Interseasonal and interspecies diversities of Symbiodinium density and effective photochemical efficiency in five dominant reef coral species from Luhuitou fringing reef, northern South China Sea - Xu, Lijia; Yu, Kefu; Li, Shu; Liu, Guohui; Tao, Shichen; Shi, Qi; Chen, Tianran; Zhang, Huiling (Coral reefs, 2017)
Although it is well established that different coral species have different susceptibilities to thermal stress, the reasons behind this variation are still unclear. In this study, 384 samples across five dominant coral species were collected seasonally between September 2013 and August 2014 at Luhuitou fringing reef in Sanya, Hainan Island, northern South China Sea, and their algal symbiont density and effective photochemical efficiency ( Φ PSII ) were measured. The results indicated that both the Symbiodinium density and Φ PSII of corals were subject to significant interspecies and seasonal variations. Stress-tolerant coral species, including massive Porites lutea and plating Pavona decussata , had higher symbiont densities but lower Φ PSII compared to the vulnerable branching species of Acropora over the course of all four seasons. Seasonally, coral symbiont densities were the lowest during winter, while during the same period, Φ PSII of corals was at the highest point. Further analysis suggested that dissolved inorganic nutrients and upwelling in the reef area were probably responsible for the observed seasonal variations in symbiont density. The fact that Porites lutea has the lowest Φ PSII during all four seasons is likely related to their symbionts’ lower capacity to provide required photosynthates for calcification. These results suggest that a coral’s thermal tolerance is primarily and positively dependent on its symbiont density and is less related to its effective photochemical efficiency.